A method for preparing Cu (II) ion imprinted assisted polyamide nanofiltration membrane for magnesium-lithium separation

CN122937650APending Publication Date: 2026-10-20TIANJIN POLYTECHNIC UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610720434.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-12
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

常规的具有较强正电密度的NF膜能在一定程度上改善Mg2+的截留和Mg2+/Li+的选择性,但强的Donnan效应也会增加Li+的排斥,导致Li+的渗透性变差,限制了Mg2+/Li+的选择性

Benefits of technology

[0021]1、本发明通过在界面聚合过程中引入Cu(II)离子,利用Cu(II)与PEI胺基的配位作用调控聚合反应动力学,经盐酸洗脱后在聚酰胺层中形成亚纳米级印迹孔道;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention provides a method for preparing a Cu(II) ion-imprinted assisted polyamide nanofiltration membrane for magnesium-lithium separation, belonging to the field of magnesium-lithium separation and ion imprinting technology. This invention introduces ion imprinting technology into an interfacial polymerization method to prepare a metal ion-imprinted composite membrane for magnesium-lithium separation in salt lake brine. The method includes the following steps: preparing a polyethersulfone-based membrane; selecting Cu(II) ions, which are between the hydration radii of magnesium and lithium ions, as template ions, adding them to a polyethyleneimine aqueous solution, and interfacially polymerizing them with trimesoyl chloride to construct a polyamide separation layer on the surface of the polyethersulfone-based membrane; eluting the template ions with hydrochloric acid to form ion-imprinted channels with specific recognition capabilities in the polyamide separation layer. This invention combines interfacial polymerization and ion imprinting technology, resulting in a simple preparation process that does not require complex multi-step modifications or expensive functional monomers, leading to low cost. It exhibits excellent separation performance under high magnesium-to-lithium ratio conditions and has promising application prospects in lithium extraction from salt lake brine.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention belongs to the field of magnesium-lithium separation and ion imprinting technology, specifically relating to a method for preparing Cu(II) ion-imprinted assisted polyamide nanofiltration membranes for magnesium-lithium separation. [Background Technology]

[0002] With the rapid growth of global demand for lithium resources, especially in high-tech fields such as electric vehicles and battery energy storage, lithium extraction and separation have become critical issues that urgently need to be addressed. Nanofiltration membrane technology, due to its high selectivity and low energy consumption during separation, has emerged as a potential solution. NF membranes, prepared through interfacial polymerization with nanoscale pores and a highly hydrophilic polyamide layer, exhibit excellent performance in ion separation. Compared to other nanofiltration membrane preparation methods (such as sol-gel, phase inversion, and layer-by-layer self-assembly), interfacial polymerization offers numerous advantages, including controllable separation layer thickness, high selectivity, strong chemical controllability, applicability to various support layers, and lower industrial production costs. Conventional NF membranes with high positive charge density can, to some extent, improve the separation performance of Mg. 2+ Retention and Mg 2+ / Li + The selectivity is high, but the strong Donnan effect also increases the Li + The rejection led to Li + The decreased permeability limited Mg 2+ / Li + The selectivity of Mg. Therefore, how to maintain the selectivity of Mg 2+ High retention while promoting Li + Ion imprinting has become a new problem that urgently needs to be solved. Ion imprinting is a selective separation technique that simulates the mechanism of biological recognition. Its basic principle is to introduce target ions as template ions into the polymer matrix, and use the chemical or physical interaction between monomer molecules and template ions to form imprinted cavities in the polymer with specific recognition capabilities, which have specific recognition capabilities for ions.

[0003] Therefore, this study combines interfacial polymerization and ion imprinting techniques, selecting ions with hydration radii between Mg2+ and Mg2+. 2+ and Li + The Cu(II) atoms between the ions serve as template ions in the imprinting process, constructing ion-imprinted channels in the polyamide layer to improve the Mg... 2+ / Li + This provides a simpler and more efficient new method for improving separation efficiency and the permeation performance of NF membranes. [Summary of the Invention]

[0004] The purpose of this invention is to address the issue that the strong Donnan effect in positively charged nanofiltration membranes prepared by existing technologies increases the Li...+ The rejection led to Li + The deterioration of Mg transport and enrichment directly affects the Mg 2+ / Li + Separation process Li + This addresses the issue of recovery efficiency. Therefore, a method for preparing Cu(II) ion-imprinted assisted polyamide nanofiltration membranes for magnesium-lithium separation is provided.

[0005] This invention selects a region between the hydration radii of magnesium and lithium ions during the interfacial polymerization process. of Cu(II) Ions as Template ions, Adding Cu(II) to an aqueous polyethyleneimine solution and interfacially polymerizing it with trimesoyl chloride, a polyamide separation layer is constructed on the surface of a polyethersulfone-based membrane. Template ions are eluted with hydrochloric acid, forming ion-imprinted channels with specific recognition capabilities within the polyamide separation layer. This invention utilizes ion imprinting technology to assist the interfacial polymerization process, enabling the Cu(II)-formed channels to improve permeability while simultaneously promoting Li… + The permeation of Mg was achieved by utilizing the Donnan effect and the synergistic effect of size sieving and imprinting in nanofiltration. 2+ / Li + Selective separation.

[0006] This invention uses polyethyleneimine as the aqueous solution monomer in the interfacial polymerization process, trimesoyl chloride as the organic phase monomer in the interfacial polymerization process, and sodium dodecyl sulfate as the surfactant. An ion-imprinted polyamide nanofiltration membrane with sub-nanometer pore sizes is prepared on a polyethersulfone ultrafiltration membrane using ion-imprinted technology-assisted interfacial polymerization. This work investigates the optimal Mg content during the interfacial polymerization process. 2+ / Li + Key preparation parameters for separation performance. For the preparation of Mg 2+ / Li + A simpler and more efficient new method is provided to separate and improve the permeation performance of NF membranes.

[0007] The specific steps are as follows:

[0008] a) Dry the polyethersulfone particles in an electric heating drying oven and cool them to room temperature. Add polyvinylpyrrolidone to a beaker, then add N-methylpyrrolidone solvent and stir until completely dissolved. Add the polyethersulfone particles in batches until completely dissolved, and continue stirring for 6–8 hours. Let it stand for 12–24 hours to obtain the casting solution. Pour the casting solution onto a clean glass plate and use a spatula to evenly coat the glass plate with the casting solution. Then, quickly immerse the glass plate in deionized water to perform a phase inversion, obtaining the polyethersulfone ultrafiltration membrane.

[0009] b) The polyethersulfone ultrafiltration membrane was immobilized in a self-made polytetrafluoroethylene frame. Sodium dodecyl sulfate and CuSO4 solution were added to an aqueous solution of polyethyleneimine to form a complex. The complex solution was poured onto the surface of the polyethersulfone ultrafiltration membrane, and after the reaction, the membrane was poured off and excess solution was absorbed with filter paper. The membrane was allowed to dry at room temperature for 5–60 min. A prepared trimesoyl chloride / n-hexane solution was poured onto the membrane surface, and after reacting for 10–60 s, the solution was poured off. The membrane was then heat-treated at 40–90°C for 5–20 min. After heat treatment, the membrane was repeatedly eluted with 1 mol / L hydrochloric acid until no Cu(II) was detected in the eluent. The membrane was then washed with water until the solution was neutral, yielding a Cu(II) ion-imprinted polyamide nanofiltration membrane. The prepared Cu(II) ion-imprinted polyamide nanofiltration membrane was stored in deionized water for later use. The same steps were used to prepare a non-imprinted polyamide nanofiltration membrane without adding CuSO4 solution.

[0010] c) A cross-flow filtration device was used. Before testing, the membrane was pre-pressed at room temperature for 30 minutes. Mg was used separately. 2+ / Li + Mixed solutions with mass ratios of 10:1, 20:1, 40:1, 60:1, and 120:1 were used as feed solutions for separation performance testing. The Mg content in the feed solution and permeate was analyzed using flame atomic absorption spectrometry. 2+ and Li + Concentration determination. The water permeability of nanofiltration membranes is 3–7 L / (m²). 2 The rejection rate of MgCl2 was 92-98% (·h·bar), and the rejection rate of LiCl was -14.76-85.87%, with a resolution of 30.34-51.53.

[0011] The polyethersulfone ultrafiltration membrane of this invention has a thickness of 100–1000 μm, an average pore size of 0.04–1 μm for the porous support membrane, and a pure water flux of 100–500 L / (m³) at room temperature and an operating pressure of 1 bar. 2 ·h).

[0012] The mass ratio of polyethersulfone, polyvinylpyrrolidone and N-methylpyrrolidone in this invention is 33:7:160, and the stirring time is 6-8 hours.

[0013] The polyethyleneimine described in this invention is one or more of branched polyethyleneimine, linear polyethyleneimine, and ethylenediamine-terminated polyethyleneimine, with a molecular weight of 600 to 10,000 and a mass concentration of 0.8 to 1.6%.

[0014] The sodium dodecyl sulfate concentration of the present invention is 0.25-0.45%, the Cu(II) solution concentration is 0.008-0.032%, and the reaction time is 5-20 min.

[0015] The mass ratio of pyromellitic methyl chloride to n-hexane in this invention is 0.20–0.35% (w / v).

[0016] The hydrochloric acid solution described in this invention is a 1 mol / L solution used in 100 mL elutions each time, preferably eluted 3 to 6 times.

[0017] The present invention discloses a method for preparing Cu(II) ion-imprinted assisted polyamide nanofiltration membrane for magnesium-lithium separation, characterized in that the ion-imprinted polyamide nanofiltration membrane is used for magnesium-lithium separation under high magnesium-lithium ratio.

[0018] The ion-imprinted polyamide nanofiltration membrane of this invention has a thin separation layer, exhibiting a unique porous structure with an average pore size smaller than Mg. 2+ The radius of hydrated ions. At a total salt concentration of 2000 mg / L, Mg... 2+ / Li + In a mixed solution with a mass ratio of 120:1, Mg 2+ The retention rate was 95.16%–96.79%, Li + Retention rate: -79.59% to -85.87%, Mg 2+ / Li + The resolution can reach 39.59–49.13. After one stage of nanofiltration, the Mg in the mixed solution... 2+ / Li + The mass ratio decreased from 120 to 2.06–2.32. After continuous operation at 4 bar for 72 hours, the resolution remained above 30. The membrane surface is negatively charged; based on the Donnan effect and the principle of transmembrane electroneutrality, when Mg... 2+ During membrane retention, in order to maintain electroneutrality on the permeate side, Cl - Transmembrane migration will drag Li + Co-permeation leads to Li in the permeate + The concentration is higher than that of the feed solution, resulting in a negative rejection. Simultaneously, the counterion competition mechanism causes Mg... 2+ When Li accumulates on the membrane surface, it leads to Li + Partial dehydration reduces the hydration radius, further promoting its penetration.

[0019] The ion-imprinted polyamide nanofiltration membrane described in this invention, through the construction of ion-imprinted channels, not only accelerates water transport but also significantly improves Mg... 2+ and Li + The separation effect.

[0020] The beneficial effects of this invention are:

[0021] 1. This invention introduces Cu(II) ions during the interfacial polymerization process and utilizes the coordination effect of Cu(II) with PEI amine groups to regulate the polymerization reaction kinetics. After elution with hydrochloric acid, sub-nanometer imprinted channels are formed in the polyamide layer.

[0022] 2. Although traditional positively charged nanofiltration membranes can enhance the protection of Mg... 2+ The electrostatic repulsion of Li is strong, but the strong Donnan effect simultaneously increases the electrostatic repulsion of Li. + The rejection led to Li + Poor permeability. This invention utilizes the Cu(II) imprinted channels and the negative charge on the membrane surface, through size sieving effect, Donnan effect and ion imprinting effect, to make Li... + In Mg 2+ When trapped, it is accompanied by Cl- co-transmembrane migration, which promotes the Li in the permeate. + The concentration is higher than that of the feed liquid;

[0023] 3. This invention uses a combination of interfacial polymerization and ion imprinting technology to prepare polyamide nanofiltration membranes. The preparation process is simple, does not require complex multi-step modification or expensive functional monomers, and is low in cost.

[0024] 4. The ion-imprinted polyamide nanofiltration membrane prepared by this invention still maintains effective separation under high salt and high magnesium-lithium ratio conditions of 2000 mg / L and 120:1 by mass, demonstrating good adaptability to the complex system of salt lake brine.

Detailed Implementation Methods

[0025] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; and the experimental methods described are conventional methods.

[0026] The present invention will be described in detail below with reference to the embodiments, but the present invention is not limited to the embodiments.

[0027] Example 1.

[0028] The preparation of a Cu(II) ion-imprinted assisted polyamide nanofiltration membrane for magnesium-lithium separation includes the following steps:

[0029] a) Dry the polyethersulfone particles in an electric hot air drying oven and cool to room temperature. Add 1.75g ​​of polyvinylpyrrolidone to a beaker, then add 40g of N-methylpyrrolidone and stir until completely dissolved. Add 8.25g of polyethersulfone particles in batches until completely dissolved, continue stirring for 6 hours, and let stand for 24 hours to obtain the casting solution. Pour the casting solution onto a clean glass plate, use a spatula to evenly coat the glass plate with the casting solution, and then quickly immerse the glass plate in deionized water to undergo phase inversion, obtaining the polyethersulfone ultrafiltration membrane.

[0030] b) The polyethersulfone ultrafiltration membrane was immobilized in a self-made polytetrafluoroethylene frame. Sodium dodecyl sulfate and Cu(II) ion solution were added to a branched polyethyleneimine (molecular weight: 600) aqueous solution at concentrations of 0.25%, 0.008%, and 1.6%, respectively. After complexation, the solution was poured onto the surface of the polyethersulfone ultrafiltration membrane. After standing, excess solution was poured off and absorbed with filter paper. The membrane was allowed to dry at room temperature for 30 min. A 0.25% pyromellitic acid / n-hexane solution was poured onto the membrane surface. After reacting for 40 s, the solution was poured off, and the membrane was heat-treated at 90 °C for 10 min. After heat treatment, the membrane was eluted with 100 mL of 1 mol / L hydrochloric acid until no Cu(II) was detected in the eluent. The membrane was then washed with water until the solution was neutral, yielding a Cu(II) ion-imprinted polyamide nanofiltration membrane. The prepared Cu(II) ion-imprinted polyamide nanofiltration membrane was stored in deionized water for later use. Using the same steps, non-imprinted polyamide nanofiltration membranes were prepared without the addition of Cu(II).

[0031] c) A cross-flow filtration device was used. Before testing, the membrane was pre-pressed at room temperature for 30 minutes. Mg was used separately. 2+ / Li + A mixed solution with a mass ratio of 120:1 was used as the feed liquid. Separation performance tests were conducted, and flame atomic absorption spectrometry was used to analyze the Mg content in the feed liquid and permeate. 2+ and Li + Concentration determination. The water permeability of the ion-imprinted polyamide nanofiltration membrane is 6.28 L / (m³). 2 The membrane exhibited a MgCl₂ rejection rate of 95.86% and a LiCl rejection rate of -64.35% (·h·bar), achieving a resolution of 39.69. The water permeability of the non-imprinted membrane was 2.31 L / (m²·bar). 2 The rejection rate for MgCl2 was 96.84%, the rejection rate for LiCl was 20.68%, and the resolution was 25.10.

[0032] Example 2.

[0033] The preparation of a Cu(II) ion-imprinted assisted polyamide nanofiltration membrane for magnesium-lithium separation includes the following steps:

[0034] a) Dry the polyethersulfone particles in an electric hot air drying oven and cool to room temperature. Add 3.5g of polyvinylpyrrolidone to a beaker, then add 80g of N-methylpyrrolidone and stir until completely dissolved. Add 16.5g of polyethersulfone particles in batches until completely dissolved, continue stirring for 8 hours, and let stand for 16 hours to obtain the casting solution. Pour the casting solution onto a clean glass plate, use a spatula to evenly coat the glass plate with the casting solution, and then quickly immerse the glass plate in deionized water to undergo phase inversion, obtaining the polyethersulfone ultrafiltration membrane.

[0035] b) The polyethersulfone ultrafiltration membrane was immobilized in a self-made polytetrafluoroethylene frame. Sodium dodecyl sulfate and CuSO4 solution were added to an aqueous solution of linear polyethyleneimine (molecular weight: 1800) at concentrations of 0.45%, 0.016%, and 0.8%, respectively. After complexation, the solution was poured onto the surface of the polyethersulfone ultrafiltration membrane. After standing, excess solution was poured off and absorbed with filter paper. The membrane was allowed to dry at room temperature for 60 min. A 0.15% pyromellitic acid / n-hexane solution was poured onto the membrane surface. After reacting for 60 s, the solution was poured off, and the membrane was heat-treated at 60 °C for 10 min. After heat treatment, the membrane was eluted with 100 mL of 1 mol / L hydrochloric acid until no Cu(II) was detected in the eluent. The membrane was then washed with water until the solution was neutral, yielding a Cu(II) ion-imprinted polyamide nanofiltration membrane. The prepared Cu(II) ion-imprinted polyamide nanofiltration membrane was stored in deionized water for later use. The same steps were used to prepare non-imprinted polyamide nanofiltration membranes without adding Cu(II) solution.

[0036] c) A cross-flow filtration device was used. Before testing, the membrane was pre-pressed at room temperature for 30 minutes. Mg was used separately. 2+ / Li + A 60:1 mass ratio mixed solution was used as the feed liquid. Separation performance tests were conducted, and flame atomic absorption spectrometry was used to analyze the Mg content in the feed liquid and permeate. 2+ and Li + Concentration determination. The water permeability of the ion-imprinted polyamide nanofiltration membrane is 5.82 L / (m³). 2 The membrane exhibited a MgCl2 rejection rate of 96.15% and a LiCl rejection rate of -85.87% (·h·bar), achieving a separation degree of 48.27. The water permeability of the non-imprinted membrane was 3.12 L / (m³). 2 The rejection rate for MgCl2 was 96.24%, the rejection rate for LiCl was 18.51%, and the resolution was 21.67.

[0037] Example 3.

[0038] The preparation of a Cu(II) ion-imprinted assisted polyamide nanofiltration membrane for magnesium-lithium separation includes the following steps:

[0039] a) Dry the polyethersulfone particles in an electric hot air drying oven and cool to room temperature. Add 7g of polyvinylpyrrolidone to a beaker, then add 160g of N-methylpyrrolidone and stir until completely dissolved. Add 33g of polyethersulfone particles in batches until completely dissolved, continue stirring for 7 hours, and let stand for 12 hours to obtain the casting solution. Pour the casting solution onto a clean glass plate, use a spatula to evenly coat the glass plate with the casting solution, and then quickly immerse the glass plate in deionized water to undergo phase inversion, obtaining the polyethersulfone ultrafiltration membrane.

[0040] b) The polyethersulfone ultrafiltration membrane was immobilized in a self-made polytetrafluoroethylene frame. Sodium dodecyl sulfate and CuSO4 solution were added to an aqueous solution of ethylenediamine-terminated polyethyleneimine (molecular weight: 800) at concentrations of 0.35%, 0.032%, and 1.2%, respectively. After complexation, the solution was poured onto the surface of the polyethersulfone ultrafiltration membrane. After standing, excess solution was poured off and absorbed with filter paper. The membrane was allowed to dry at room temperature for 15 min. A 0.35% pyromellitic acid / n-hexane solution was poured onto the membrane surface. After reacting for 20 s, the solution was poured off, and the membrane was heat-treated at 40 °C for 20 min. After heat treatment, the membrane was eluted with 100 mL of 1 mol / L hydrochloric acid until no Cu(II) was detected in the eluent. The membrane was then washed with water until the solution was neutral, yielding a Cu(II) ion-imprinted polyamide nanofiltration membrane. The prepared Cu(II) ion-imprinted polyamide nanofiltration membrane was stored in deionized water for later use. The same steps were used to prepare non-imprinted polyamide nanofiltration membranes without adding Cu(II) solution.

[0041] c) A cross-flow filtration device was used. Before testing, the membrane was pre-pressed at room temperature for 30 minutes. Mg was used separately. 2+ / Li + A 20:1 mass ratio mixed solution was used as the feed solution for separation performance testing. Flame atomic absorption spectrometry was used to analyze the Mg content in the feed solution and permeate. 2+ and Li + Concentration determination. The water permeability of the ion-imprinted polyamide nanofiltration membrane is 4.98 L / (m³). 2 The membrane exhibited a MgCl2 rejection rate of 96.58% and a LiCl rejection rate of -76.24% (·h·bar), achieving a resolution of 51.53. The water permeability of the non-imprinted membrane was 2.16 L / (m³). 2 The rejection rate for MgCl2 was 97.64%, the rejection rate for LiCl was 25.49%, and the resolution was 31.57.

Claims

1. A method for preparing Cu(II) ion-imprinted assisted polyamide nanofiltration membranes for magnesium-lithium separation, characterized in that... The method is performed according to the following steps: a1. Dry the polyethersulfone particles in an electric heating drying oven and cool them to room temperature for later use. Add polyvinylpyrrolidone to a beaker, add N-methylpyrrolidone solvent to the beaker and stir until completely dissolved. Add the polyethersulfone particles in batches until completely dissolved, continue stirring for 6-8 hours, and let stand for 12-24 hours to obtain the casting solution. Pour the casting solution onto a clean glass plate, use a spatula to evenly coat the glass plate with the casting solution, and then quickly immerse the glass plate in deionized water to carry out phase inversion to obtain the polyethersulfone ultrafiltration membrane. b) The polyethersulfone ultrafiltration membrane was fixed in a self-made polytetrafluoroethylene frame. Sodium dodecyl sulfate and CuSO4 solution were added to an aqueous solution of polyethyleneimine to form a complex. The complex solution was poured onto the surface of the polyethersulfone ultrafiltration membrane. After the reaction, excess solution was poured off and absorbed with filter paper. The membrane was allowed to dry at room temperature for 5–60 min. A prepared pyromellitic acid / n-hexane solution was poured onto the membrane surface. After reacting for 10–60 s, the solution was poured off. The membrane was then heat-treated at 40–90 °C for 5–20 min. After heat treatment, the membrane was repeatedly eluted with 1 mol / L hydrochloric acid until no Cu(II) was detected in the eluent. The membrane was then washed with water until the solution was neutral, yielding a Cu(II) ion-imprinted polyamide nanofiltration membrane. The prepared Cu(II) ion-imprinted polyamide nanofiltration membrane was stored in deionized water for later use. The same steps were used to prepare a non-imprinted polyamide nanofiltration membrane without adding CuSO4 solution. c) A cross-flow filtration device was used. Before testing, the membrane was pre-pressed at room temperature for 30 minutes. Mg was used separately. 2+ / Li + Mixed solutions with mass ratios of 10:1, 20:1, 40:1, 60:1, and 120:1 were used as feed solutions for separation performance testing. The Mg content in the feed solution and permeate was analyzed using flame atomic absorption spectrometry. 2+ and Li + Concentration determination. The water permeability of nanofiltration membranes is 3–7 L / (m²). 2 The rejection rate of MgCl2 was 92-98% (·h·bar), and the rejection rate of LiCl was -14.76-85.87%, with a resolution of 30.34-51.

53.

2. The method for preparing a Cu(II) ion-imprinted assisted polyamide nanofiltration membrane for magnesium-lithium separation according to claim 1, characterized in that... The mass ratio of polyethersulfone, polyvinylpyrrolidone and N-methylpyrrolidone in step a) is 33:7:160, and the stirring time is 6-8 hours.

3. The method for preparing a Cu(II) ion-imprinted assisted polyamide nanofiltration membrane for magnesium-lithium separation according to claim 1, characterized in that... The polyethyleneimine mentioned in step b) is one or more of branched polyethyleneimine, linear polyethyleneimine, and ethylenediamine-terminated polyethyleneimine, with a molecular weight of 600 to 10,000 and a mass concentration of 0.8 to 1.6%.

4. The method for preparing a Cu(II) ion-imprinted assisted polyamide nanofiltration membrane for magnesium-lithium separation according to claim 1, characterized in that... In step b), the concentration of sodium dodecyl sulfate is 0.25–0.45%, the concentration of Cu(II) solution is 0.008–0.032%, and the reaction time is 5–20 min.

5. The method for preparing a Cu(II) ion-imprinted assisted polyamide nanofiltration membrane for magnesium-lithium separation according to claim 1, characterized in that... The ratio of pyromellitic methyl chloride to n-hexane in step b) is 0.20–0.35% (w / v).

6. The method for preparing a Cu(II) ion-imprinted assisted polyamide nanofiltration membrane for magnesium-lithium separation as described in claim 1, characterized in that... A polyamide nanofiltration membrane prepared with Cu(II) ion imprinting was used for magnesium-lithium separation in salt lake brines with a high magnesium-to-lithium ratio.